A cohort analysis of men with a family history of BRCA1/2 and Lynch mutations for prostate cancer. Issue 1 (December 2016) - Kerr, Lynne; Rewhorn, Matthew; Longmuir, Mark; Fraser, Sioban; Walsh, Shaun; Andrew, Nicola; Leung, Hing
Abstract Background Prostate cancer (PC) is a major health concern for men worldwide, with an estimated lifetime risk of 14 %. A recent comprehensive analysis of mutational processes revealed ageing and mismatch repair as the only altered processes in PC. We wish to test if a cohort of men with inherited risk of mismatch repair defect throughBRCA1/2 or Lynch Syndrome mutations represents a target population for prostate cancer testing. Methods Fifty-eight men (aged 40–69 years) from families with a history of BRCA1/2 or HNPCC/Lynch mutations were invited to take part. Men with PSA >3.0 ng/ml were recommended to have transrectal ultrasound-guided prostatic biopsies. Results Overall 1 of 7 (14 %) and 1 of 20 (5 %) men withBRCA1/2 mutations were positive for a diagnosis of prostate cancer. In men with Lynch syndrome, 1 of 4 (25 %) was diagnosed to have prostate cancer. The index case with Lynch syndrome harbours a heterozygous mutation in the mismatch repairMSH6 gene. Near to complete loss of MSH6 immunoreactivity in the prostate tumour supports silencing of the remainingMSH6 allele during prostate carcinogenesis. Conclusion The finding of near-to-complete loss of MSH6 expression in affected men with a family history of Lynch Syndrome supports its mechanistic involvement during prostate carcinogenesis. This work therefore contributes to the argument that, in certain male populations, Lynch Syndrome mutations are biologically implicated in men with prostate cancer.